The impacts of COVID-19, meteorology, and emission control policies on PM2.5 drops in Northeast Asia - Kang, Yoon Hee; You, Seunghee; Bae, Minah; Kim, Eunhye; Son, Kyuwon; Bae, Changhan; Kim, Yoonha; Kim, Byeong Uk; Kim, Hyun Cheol; Kim, Soontae (Scientific Reports, 2020)
In January 2020, anthropogenic emissions in Northeast Asia reduced due to the COVID-19 outbreak. When outdoor activities of the public were limited, PM2.5 concentrations in China and South Korea between February and March 2020 reduced by − 16.8 μg/m3 and − 9.9 μg/m3 respectively, compared with the average over the previous three years. This study uses air quality modeling and observations over the past four years to separate the influence of reductions in anthropogenic emissions from meteorological changes and emission control policies on this PM2.5 concentration change. Here, we show that the impacts of anthropogenic pollution reduction on PM2.5 were found to be approximately − 16% in China and − 21% in South Korea, while those of meteorology and emission policies were − 7% and − 8% in China, and − 5% and − 4% in South Korea, respectively. These results show that the influence on PM2.5 concentration differs across time and region and according to meteorological conditions and emission control policies. Finally, the influence of reductions in anthropogenic emissions was greater than that of meteorological conditions and emission policies during COVID-19 period.
Keywords: Air Pollutants; Air Pollution; China; COVID-19; Environmental Monitoring; Environmental Pollution; Humans; Meteorology; Particulate Matter; Republic of Korea; SARS-CoV-2; Vehicle Emissions